Bioremediation of polycyclic aromatic hydrocarbons by bacterial strains isolated from petroleum contaminated soil - Mustaffa, Nooraidah; Jamal, Parveen; Saheed, Olorunnisola Kola; Kabashi, Nassereldeen A.; Ali, Fathilah; Othman, Rashidi; Redzwan, Ghufran (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Spillage or dumping of petroleum and its product onto the land are among the main sources of polycyclic aromatic hydrocarbons existence in the soil. These hydrocarbons could act as sole carbon and energy sources for certain indigenous bacteria. Ability of bacteria to consume such substrate could help reducing the amount of highly toxic contaminant including petroleum hydrocarbon. This study is aimed to acquire effective bacteria which could consume and transform polycyclic aromatic hydrocarbon (PAH) to be used for the treatment of PAH contaminated soil. In this study, twelve strains of bacteria were successfully isolated from the petroleum contaminated soil. Soil samples were collected from three different sites, which are automobile workshop (SU), petrol station PJ and busy roadside (WS). All the twelve isolated bacteria and a commercially available bacteria, Pseudomonas Putida (PP) were then tested on their ability to degrade PAH by using phenanthrene (a three ring polycyclic PAH) which selected to be the model polycyclic PAH. The ability of bacteria in degrading phenanthrene was elucidated qualitatively with profound metabolism of the soil contaminants. Early stage of this study, found that all isolates and the commercial bacteria were able to grow on the agar plate sprayed with phenanthrene. The growth indicated that the bacteria are able to mineralize phenanthrene. Bacteria strain SU4 and Pseudomonas Putida showed the greatest growth to signify as the highest metabolic versatility as compared to other strains bacteria. Identification of the taxonomy of such effective bacteria will further assist in understanding its role, function and mechanism of the microbial bioremediation of PAH contaminated soil. This knowledge shall lead to another promising method for removal of PAH from the soil, especially when contaminated land is to be redeveloped for human purposes.